Non-Bank Sharia Housing Purchasing Decision Segment: Is a Sustainable Halal Lifestyle Important as Moderation? - Erike Anggraeni; Normasyhuri, Khavid; Siti Nurohmah (AL-MUZARA'AH, 2024)
Researchers focus on looking at the relationship between price and digital marketing and whether a sustainable halal lifestyle can strengthen or weaken non-bank sharia-based housing purchase decision making. Quantitative in this study using SmartPLS 3.0. Primary data was collected from respondents, namely consumers of non-bank Islamic housing by taking samples using purposive sampling and using 500 samples. Data is collected by accessing the Google form and the indicator measurement is the Likert scale. The results of the study provide the fact that price and digital marketing have a positive relationship with non-bank sharia housing purchase decisions. A sustainable halal lifestyle strengthens the relationship between price and digital marketing on purchasing decisions for non-bank sharia housing. This study is expected to be able to identify market opportunities and provide a reference for sharia housing developers to be able to develop housing concepts that are innovative and in line with market demands and understand and respond to the needs and preferences of buyers who live a halal lifestyle.